2017
DOI: 10.1055/s-0043-111587
|View full text |Cite
|
Sign up to set email alerts
|

Semimembranosus Muscle Injuries In Sport. A Practical MRI use for Prognosis

Abstract: The aim of this work was to study semimembranosus musculotendinous injuries (SMMTI) and return to play (RTP). The hypothesis is that some related anatomic variables of the SM could contribute to the prognosis of RTP. The retrospective study was done with 19 athletes who suffered SMMTI from 2010 to 2013 and in whose cases a 3.0T MRI was performed. We evaluated the A, B, C SM regions damaged and calculated the relative length and percentage of cross-sectional area (CSA) affected. We found the correlation of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Clinically, it is sometimes difficult to precisely locate the lesion, and in these circumstances MRI plays a key role. Knowledge of some anatomical characteristics of the distribution of connective tissue and the orientation of fascicles/fibers in these muscle groups [13][14][15][16][17][18][19][20] is crucial for accurately interpreting the MRI findings in the diagnosis of muscle injuries of the lower limbs.…”
Section: Mechanisms Of Injury and Muscle Anatomical Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinically, it is sometimes difficult to precisely locate the lesion, and in these circumstances MRI plays a key role. Knowledge of some anatomical characteristics of the distribution of connective tissue and the orientation of fascicles/fibers in these muscle groups [13][14][15][16][17][18][19][20] is crucial for accurately interpreting the MRI findings in the diagnosis of muscle injuries of the lower limbs.…”
Section: Mechanisms Of Injury and Muscle Anatomical Featuresmentioning
confidence: 99%
“…Although the proximal tendon anatomy is complex and there may be common components to the tendon origins, the adductor longus is the most frequently injured of the three. Adductor longus is a fan-shaped muscle, which arises from the anterior aspect of the pubis just inferior to the pubic tubercle and expands to attach to the middle third of the linea aspera of the femur [18,20]. The proximal tendon is short and conforms an intramuscular aponeurosis.…”
Section: Adductorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Slavotenik et al, found an 87% (26 out of 30 elite soccer players) incidence rate for injuries to the LHBF, and 17% (5 out of 30 cases) to the short head of the biceps [3]. Interestingly, injuries affecting the BF have been associated with faster recoveries than those involving the SM [6,19]. Anatomical features have been previously described and could justify the difference in prevalence of injury between the muscles of the hamstrings complex [4,6,7,20,21].…”
Section: Discussionmentioning
confidence: 99%